1996
DOI: 10.1101/gad.10.7.887
|View full text |Cite
|
Sign up to set email alerts
|

Multiprotein transcription factor UAF interacts with the upstream element of the yeast RNA polymerase I promoter and forms a stable preinitiation complex.

Abstract: Like most eukaryotic rDNA promoters, the promoter for rDNA in Saccharomyces cerevisiae consists of two elements: a core element, which is essential, and an upstream element, which is not essential but is required for a high level of transcription. We have demonstrated that stimulation of transcription by the upstream element is mediated by a multiprotein transcription factor, UAF (upstream activation factor) which contains three proteins encoded by RRN5, RRN9, and RRN10 genes, respectively, and probably two ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
182
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(192 citation statements)
references
References 62 publications
9
182
1
Order By: Relevance
“…First, it is formed by several hundreds of tandem repeats of about 10 kb in yeast that cluster together to form the nucleolus [1]. Second, promoters contain two main regions termed upstream element (UE) and core element (CE) in yeast, with the latter overlapping with the transcription start site and the former extending to about 150 bp upstream of this site [2]. Third, in actively growing cells rDNA transcription represents 60% of the total transcriptional activity [3], which correlates with a high content of RNA polymerase occupancy on rDNA genes [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it is formed by several hundreds of tandem repeats of about 10 kb in yeast that cluster together to form the nucleolus [1]. Second, promoters contain two main regions termed upstream element (UE) and core element (CE) in yeast, with the latter overlapping with the transcription start site and the former extending to about 150 bp upstream of this site [2]. Third, in actively growing cells rDNA transcription represents 60% of the total transcriptional activity [3], which correlates with a high content of RNA polymerase occupancy on rDNA genes [4].…”
Section: Introductionmentioning
confidence: 99%
“…The upstream activating factor (UAF) binds the UE [2], while the core factor (CF) binds the CE [8]. The two protein complexes interact with each other and are bridged through TATA-box binding protein (TBP) binding [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of 64% deletion, all four spores were viable and formed colonies after 4 days of incubation at 30uC; however, the disruption of 80% of ORF YLR141w yielded only two viable spores, indicating that YLR141w is an essential gene. In contrast, Keys et al (1996) reported that RRN5 deletion is not lethal because all spores from the rrn5D/RRN5 diploid were capable of forming colonies. The spores containing the disruption normally formed two microcolonies only after 10 days of incubation, although sometimes only one or neither of the spores grew.…”
Section: Resultsmentioning
confidence: 94%
“…Tetrad analysis showed that such deletions were not lethal and produced no apparent phenotype in the haploid cell. Keys et al (1996) reported that YLR141w is the RRN5 gene, an RNA polymerase I-specific transcription factor, whose function is not essential but is required for high level of transcription. This prompted a further deletion of 200 bp more of the upstream region of ORF YLR141w, resulting in a total of 78% disruption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation